2017
DOI: 10.5138/09750185.1920
|View full text |Cite
|
Sign up to set email alerts
|

In- vivo diuretic and antiulcer activity in fruits of <em>Buchanania lanzan</em>

Abstract: <p><strong>Ethnopharmacological relevance:</strong> The fruits of <em>Buchanania lanzan</em> are used traditionally in the treatment of skin afflictions, sores, ulcers, inflammation and as diuretic (1,21,35,42). The aim of the study was to investigate the antiulcer and diuretic activity of the crude ethanolic and pet. ether extract from the fruits of <em>Buchanania lanzan</em>.</p><p><strong>Materials and methods:</strong> The antiulcer activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…roots. Tyagi et al, 10 reported in-vivo diuretic and anti-ulcer activity in fruits of Buchanania lanzan.…”
mentioning
confidence: 99%
“…roots. Tyagi et al, 10 reported in-vivo diuretic and anti-ulcer activity in fruits of Buchanania lanzan.…”
mentioning
confidence: 99%